2017
DOI: 10.1080/10942912.2017.1306553
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics of carotenoids and visual colour in pumpkin (Cucurbita maxima L.) slices during microwave-vacuum drying

Abstract: The degradation kinetics of colour and individual carotenoids including lutein, α-carotene and β-carotene in pumpkin slices was investigated during microwave-vacuum drying (MVD) at selected microwave powers (4-8 W/g). The contents of lutein, α-carotene and β-carotene significantly decreased, while visual colour parameters such as the Hunter L* value decreased and the total colour difference (ΔE) value increased with the increase of processing time and microwave power. Degradation of lutein, α-carotene, β-carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…Similar results were observed for commercial β-carotene encapsulated in maltodextrin ( 46 ). The degradation kinetics of carotenoids in pumpkin slices has been studied as well ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed for commercial β-carotene encapsulated in maltodextrin ( 46 ). The degradation kinetics of carotenoids in pumpkin slices has been studied as well ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…The changes of individual color coordinates (L*, a*, b* and Chroma) followed the first-order kinetics with a higher goodness-of-fit value (R 2 ) as shown in Table 3, whereas the total color difference of ΔE value followed zero-order reaction kinetics and linear regression with the coefficient of determination value (R 2 ) 0.9798. The studies on the total color difference (ΔE) of pumpkin cubes in convective drying (Song et al., 2017) and jack fruit bulb in hot air drying (Saxena et al., 2012) also concluded that the total color difference (ΔE) fitted the zero-order model.…”
Section: Resultsmentioning
confidence: 99%
“…The colour index was calculated as the a */ b * ratio [ 9 ]. The total colour difference (ΔE) was used to characterize the overall change in colour during the storage and was calculated by the following Equation (1) [ 42 ]: where , and are values of green tomatoes at day 0 (initial control).…”
Section: Methodsmentioning
confidence: 99%